- #1

- 1,196

- 1

the question is http://home.earthlink.net/~urban-xrisis/phy002.jpg [Broken]

I thought that...

[tex]F=G\frac{m_1m}{R_1^2}-G\frac{m_2m}{R_2^2}[/tex]

a.

[tex]F=G\frac{m_1m}{a^2}-G\frac{m_2m}{(R_2-a)^2}[/tex]

b.

[tex]F=G\frac{m_1m}{b^2}-G\frac{m_2m}{(R_2-b)^2}[/tex]

c.

[tex]F=G\frac{m_1m}{c^2}+G\frac{m_2m}{c^2}[/tex]

is this correct?

I thought that...

[tex]F=G\frac{m_1m}{R_1^2}-G\frac{m_2m}{R_2^2}[/tex]

a.

[tex]F=G\frac{m_1m}{a^2}-G\frac{m_2m}{(R_2-a)^2}[/tex]

b.

[tex]F=G\frac{m_1m}{b^2}-G\frac{m_2m}{(R_2-b)^2}[/tex]

c.

[tex]F=G\frac{m_1m}{c^2}+G\frac{m_2m}{c^2}[/tex]

is this correct?

Last edited by a moderator: